Socio-Cognitive Dynamics in Chemistry Education: A Vygotskian Analysis of Collaborative Learning Practices - Hassan Aliyu; Corrienna Abdul Talib (Abdurrauf Social Science, 2026)
This study evaluated the influence of a structured collaborative learning environment on secondary school students’ academic engagement and conceptual understanding in chemistry. Guided by Vygotsky’s Zone of Proximal Development, a quasi-experimental design was employed with 240 participants divided into experimental and control groups. The experimental group engaged in Jigsaw II and peer-led team learning strategies, while the control group received traditional lecture-based instruction. Data were collected using a Chemistry Performance Test, a motivation questionnaire, and classroom observations. Results indicated a statistically significant and large positive effect on academic performance for the experimental group. Collaborative learning also enhanced intrinsic motivation, self-efficacy, and the perceived value of peer interaction. However, its impact on reducing general chemistry anxiety was moderate. The findings affirm social constructivism as a viable framework for teaching complex chemical concepts and highlight the importance of specific social interaction patterns, such as peer modeling and cognitive conflict resolution, in facilitating mastery. This study provides evidence for integrating collaborative pedagogies into secondary chemistry curricula to develop both conceptual understanding and essential interpersonal competencies.